Determining the Effects on Plant Metabolites of Khairwal (Bauhinia Purpurea Linn) - Ashish Sarkar; L. P. Singh; V. D. Tripathi; Garima Mishra (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Bauhinia purpurea Linn is an ornamental plant found throughout the globe known as Khairwal in Hindi having high therapeutic value in Ayurvedic preparations. Numerous types of biological activities are attributed to bauhinia species. B. Purpurea Linn is an important species used to treat many ailments in the traditional system of medicine. The plant is popular in India, and bark was reported as antimycobacterial, antimalarial, antifungal, cytotoxic and anti-inflammatory activities. The plant is useful in diarrhoea, pain, rheumatism, inflammation, cancer, and many more medicinal purposes. Since the plant is used in various formulations commonly, its quality and quantity are of prime importance. The current study deals with the changes in chemical constituents due to different factors. For the present study, the fresh leaves of Bauhinia Purpurea linn was selected. Polyphenol content was determined spectrophotometrically. In order to determine the seasonal variation of the concentration of phenolic compounds, flavonoids, and antioxidant activity, plant materials during three different seasons and geographical conditions were analysed. The findings of the study suggested that Hydroalcoholic extracts contain strong phytochemical activity while changing different parameters. Change of season or region does affect drastically the synthesis of phytochemicals of the plant.